2018
DOI: 10.1039/c8ra06329j
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics process of a Pb(ii)/Pb(0) couple and selective fabrication of Li–Pb alloys in LiCl–KCl melts

Abstract: The electrode reaction of Pb(II) and co-reduction of Li(I) and Pb(II) were investigated on a tungsten electrode in LiCl-KCl eutectic melts by a range of electrochemical techniques. From cyclic voltammetry and square wave voltammetry measurements, the reduction of Pb(II) was found to be a one-step diffusion-controlled reversible process with the exchange of 2 electrons. The diffusion coefficients of Pb(II) were computed, and they obey the Arrhenius law. Using the linear polarization technique, the kinetic param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…2a (blue line), compared with Fig. 1, some redox signals of C/C′, I/I′, II′ and D can be observed.According to the previous result,51 C/C′ and D pertain to the reduction/dissolution of metallic Pb and the formation of Pb-Li alloy compound, respectively. However, the anodic peak D′ related to the reduction peak D does not appear, which may be that the anodic peak B' is very strong and the anodic peak D′ may be covered.…”
mentioning
confidence: 71%
“…2a (blue line), compared with Fig. 1, some redox signals of C/C′, I/I′, II′ and D can be observed.According to the previous result,51 C/C′ and D pertain to the reduction/dissolution of metallic Pb and the formation of Pb-Li alloy compound, respectively. However, the anodic peak D′ related to the reduction peak D does not appear, which may be that the anodic peak B' is very strong and the anodic peak D′ may be covered.…”
mentioning
confidence: 71%
“…The anodic/cathodic signals of V′/V detected at about −0.38/−0.40 V pertain to the dissolution and deposition of Pb metal. 50 It can be inferred from the shape of the redox signals (III/III′), that the system is soluble–soluble, and III/III′ are related with the formation/dissolution of (Li–Pb) solid solution. The deposition potential of Li on liquid Pb electrode can be seen at more positive value than that on W electrode due to the formation of (Li–Pb) solution, and process is expressed as following: Li( i ) in LiCl–KCl + e − + Pb = (Li–Pb) solution …”
Section: Resultsmentioning
confidence: 99%
“…The electrochemical reaction of lead ions reduction is reversible according to the two-valence scheme; the diffusion coefficient, calculated according to Sanda’s equation, is equal to D Pb(II) = 2.26 × l0 −5 cm 2 /s for 873 K. It is found that potentiostatic lithium reduction on the preliminary deposited lead results in the formation of a liquid Li–Pb alloy, whereas Mg–Li–Pb alloys form only after an MgCl 2 addition to the melt. Later, Han et al [ 10 ] studied the kinetics of cathode processes on the indifferent electrode at lead ions Pb 2+ reduction in the LiCl–KCl melt. Zhu [ 11 ] analyzed Pb (II) electrochemical behavior on the tungsten electrode in the molten NaCl–KCl eutectic at 700 °C using voltammetry and chronopotentiometry.…”
Section: Introductionmentioning
confidence: 99%